PENENTUAN STRATEGI PENGEMBANGAN BISNISPADA COFFEE SHOP "DOBRO COFFEE" DENGANMENGGUNAKAN METODE AHP DAN LEANCANVAS - Lutfiah Amelia Putri (2021)
Dobro Coffee is one of the newcomers in the coffee shop business. Along with the inception of many new coffee shops, one of the matters that need to be noticed by the coffee shop businessmen is how they can create a different character with the other businessmen so that it can bring more consumers and extend the existing market share. The objectives of this study were to determine and create a strategic plan of business development based on the company's internal and external factor analysis. The methods used in this research were IFE and EFE matrix, IE matrix, SWOT matrix, AHP, and lean Canvas. The result of the IE matrix indicated that Dobro Coffee was at cell II that was growing and developing. There were five alternative strategies based on the IE and SWOT matrix. On calculation using AHP, the main factor that played a role in the business development strategy was competitiveness, the main actor that had a role was Digital Marketing, and the main alternative strategy was increasing the promotion by utilizing the digital platform.